2021
DOI: 10.1371/journal.pone.0245976
|View full text |Cite
|
Sign up to set email alerts
|

SLAM-based augmented reality for the assessment of short-term spatial memory. A comparative study of visual versus tactile stimuli

Abstract: The assessment of human spatial short-term memory has mainly been performed using visual stimuli and less frequently using auditory stimuli. This paper presents a framework for the development of SLAM-based Augmented Reality applications for the assessment of spatial memory. An AR mobile application was developed for this type of assessment involving visual and tactile stimuli by using our framework. The task to be carried out with the AR application is divided into two phases: 1) a learning phase, in which pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 49 publications
(71 reference statements)
2
19
0
Order By: Relevance
“…Our proposal is totally configurable and the supervisor can customize the sounds to be used and can place them in any environment. Another little explored sense is that of touch [45]. If these senses were used individually or in combination they could be of great help for spatial memory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Our proposal is totally configurable and the supervisor can customize the sounds to be used and can place them in any environment. Another little explored sense is that of touch [45]. If these senses were used individually or in combination they could be of great help for spatial memory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The participants who were physically bullied were most likely to report sleep disorders. This may be because they received tactile, visual, and other stimuli simultaneously, which left a deeper impression on them ( 37 ). We also found that victims of cyberbullying had the highest risk of sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the effect of VR and AR spatial memory training on short-term and long-term memory, has shown that, even if VR outperforms AR in the immediate posttraining test, AR is better suitable for long-term spatial memory transfer [57]. Nonetheless, physical displacements have been shown to be important in acquiring spatial ability skills [58]. Solutions combining non-immersive VR and AR technologies also exist.…”
Section: Visualisation Technologiesmentioning
confidence: 99%
“…Touchscreen surface [3]- [5], [7], [13], [16], [19], [21], [26], [31]- [33], [36], [37], [39], [41], [43], [44], [48], [50], [58], [59], [85], [118], [121]- [127], [129]- [145], [160]- [168], [199], [225], [232] 60…”
Section: Gaming Devicesmentioning
confidence: 99%